Empowering Creative Industry Using Local Nature-Based Raw Materials: Organizational Capacity Perspective - Ayu Krishna Yuliawati; Rofi Rofaida; Suryana Suryana (AIBPM Publisher, 2019)
Handycraft industries using local nature-based raw materials have been put as a top priority in the development of creative industries in Indonesia since they significantly contribute to Indonesia's national income and employment from 2010 to 2015. The development of these industries has a great potential but there are problems associated with the low organizational capacity of the industries so that empowerment strategy through organizational capacity development is needed. The research involved creative industries using local nature-based raw materials in Bandung,West Java. The method used in this research is descriptive survey. The data collection methods used were interviews and questionnaires. Further, the research data were analyzed using descriptive analysis. The result show that handycraft industries using local nature-based raw materials need organizational capacity development. The priority areas for the organizational capacity development are: vision, mission and goal; system and infrastructure; organizational structure; and culture.